Determinants of bank technical efficiency: Evidence from rural and community banks in Ghana - Michael Adusei (Cogent Business & Management, 2016)
What are the determinants of the technical efficiency of rural and community banks in Ghana? This paper addresses this question with data from 101 rural and community banks in Ghana. Data envelopment analysis based on the variable return to scale assumption and binary logistic regression technique has been used for analysis. The results show that only 20 rural and community banks are technically efficient. The binary logistic regression analysis provides evidence that size, profitability, and bank funding quality are significant determinants of technical efficiency in the rural banking industry in Ghana. Whereas an increase in the size and funding quality of a rural bank results in a decrease in its technical efficiency, an increase in the profitability of a rural bank improves its technical efficiency. It can be inferred from these results that the resource utilization of many rural and community banks in Ghana is weak and that the resource utilization performance of a rural bank can be assessed by considering its size, profitability, and funding quality.
Keywords: 650